The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1039/b915662c
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific and highly stereoselective cyclopropanation reactions promoted by samarium

Abstract: Samarium metal and samarium diiodide have become important tools as selective cyclopropanating agents in organic synthesis due to their high chemo- and stereoselectivity. Therefore, Sm and SmI(2) are the ideal reagents to prepare cyclopropane derivatives. This tutorial review highlights C-C multiple bond cyclopropanation processes promoted by samarium or samarium diiodide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(33 citation statements)
references
References 63 publications
0
33
0
Order By: Relevance
“…This H-bond interaction likely inhibits coordination of HMPA to Sm(II). With this mechanistic insight one can rationalize the unsuccessful reduction of 4butylbenzamide (5) with Sm(II)-HMPA system (Table 3). It is interesting that the differences between TFE and isopropanol in activating TMSCl through H-bond interactions is reflected only in the case of HMPA.…”
Section: Role Of Proton Donors and H-bonding In Smi 2 Catalysismentioning
confidence: 99%
See 2 more Smart Citations
“…This H-bond interaction likely inhibits coordination of HMPA to Sm(II). With this mechanistic insight one can rationalize the unsuccessful reduction of 4butylbenzamide (5) with Sm(II)-HMPA system (Table 3). It is interesting that the differences between TFE and isopropanol in activating TMSCl through H-bond interactions is reflected only in the case of HMPA.…”
Section: Role Of Proton Donors and H-bonding In Smi 2 Catalysismentioning
confidence: 99%
“…Samarium diiodide (SmI 2 ) and related Sm(II)-based reductants are important reagents in the arsenal of synthetic chemists. [1][2][3][4][5][6][7][8][9] First introduced by Kagan and coworkers, SmI 2 is a versatile single electron reductant capable of reducing a range of functional groups under mild reaction conditions. 10 The majority of SmI 2 -based reactions are carried out in THF since the reagent is stable in this medium and is soluble up to 0.1 M. Initially considered a "specialized" reagent, a range of studies have shown that SmI 2 is capable of efficiently reducing a wide range of functional groups.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the spirocyclic oxindoles, 3spirocyclopropane-2-oxindoles represent an important class that has shown remarkable biological activities and emerged recently as potent drug candidates. [14][15][16][17][18][19][20] Among the various transition-metal catalysts used, rhodium(II) catalysts bearing carboxylate ligands are one of the most extensively studied and employed catalysts in cyclopropanation reactions. [8][9][10][11][12] Since the pioneering work of Nozaki and Noyori, 13 the transition metal-catalyzed asymmetric cyclopropanation between diazo compounds and alkenes has emerged as a powerful strategy for the synthesis of cyclopropane derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose,w ee nvisioned the reductive coupling of 4-oxo-4H-1-benzopyrans,t hrough their 2-positions,b ym eans of samarium diiodideasasingle-electron transfer (SET) reagent.Samarium diiodide [3] is unique when compared with other SET reagents given its well-known high versatility in providing different radicals in organic synthesis.I nfact, the use of samarium diiodide has been widely covered in the literature in different reductivep rocesses, [4] including homo-or heterocoupling reactions. [5] Our group has accumulated aw idee xperience in the use of samarium diiodidei nb oth ionic and radicalr eactions,i ncluding its application in 1,2-elimination processes, [6] cyclopropanation reactions [7] reduction of multiple bonds [8] and the stereoselective synthesis of compounds of high value derived from naturalp roducts such as carbohydrates [9] or aaminoa cids. [10] Encouraged by the pharmacological interest in biflavonoids, [1f] hereinw er eport the use of different easily availablef lavanones as startingm aterials for the stereoselective synthesiso fb iflavonoids through as amarium diiodidepromoted and temperature-depending stereodivergent radical-coupling reaction.Initial reactions were performed on commercially available flavone 1a at room temperature.T hus, treatment of flavone 1a (1.0 equiv) dissolved in THF and the use of methanol (1.25 equiv) as the co-solvent with a0 .…”
mentioning
confidence: 99%